Estimation of received signals at arbitrary remote locations based on estimation of arriving waves by compressed sensing - Sugimoto, Tomoya; Iwai, Hisato; Sasaoka, Hideichi (2016 International Symposium on Antennas and Propagation (ISAP), 2016)
Propagation characteristics have locality in a multipath fading environment. The locality is utilized for various techniques using radio wave. Recently, on the other hand, new techniques to break the locality have been studied. In the techniques, received signals at arbitrary locations are estimated from remote receiving points. We present in this paper a new estimation technique of received signals utilizing Compressed Sensing (CS). In the technique, we estimate directions of arrival and each complex amplitude of arriving waves by CS, and calculate a received signal at a remote location based on the estimated results. We present the technique and evaluate the estimation performance through computer simulations.